1998
DOI: 10.1152/ajplung.1998.275.1.l103
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor mRNA and protein in fetal rat lung in vivo: modulation by glucocorticoid and androgen

Abstract: Pulmonary glucocorticoid receptor (GR) is essential to timely preparation for the onset of breathing air at birth. We have previously used primary culture of late-gestation fetal rat lung cells to demonstrate differential regulation of GR by glucocorticoid depending on cell type. In this study, we hypothesized that the action of glucocorticoid on GR mRNA expression and protein elaboration in lung cells might be modulated by interactions present in vivo but not in primary culture. Given that male sex hormone (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 47 publications
5
19
1
Order By: Relevance
“…These in vivo findings (Figs. 8. and 9) support previously described studies in fetal and adult rat lung demonstrating that exogenous GC can either up-or downregulate the level of their own receptor by a variety of mechanistic pathways including transcriptional, posttranscriptional, and translational (28,29,49).…”
Section: Regulation Of Gcr Protein By Dex In 29-day Ga Preterm Rabbitsupporting
confidence: 81%
See 4 more Smart Citations
“…These in vivo findings (Figs. 8. and 9) support previously described studies in fetal and adult rat lung demonstrating that exogenous GC can either up-or downregulate the level of their own receptor by a variety of mechanistic pathways including transcriptional, posttranscriptional, and translational (28,29,49).…”
Section: Regulation Of Gcr Protein By Dex In 29-day Ga Preterm Rabbitsupporting
confidence: 81%
“…One particular gene regulated by GC is the GCR gene itself (17,28,29,49). A change in the expression of basal levels of GCR in either whole tissue or isolated cell culture by exogenous GC is described as autoregulation (28)(29)(30)49). In these particular studies we observed that treatment of 29-day GA preterm rabbits with Dex for 8 h did not greatly alter whole lung GCR mRNA expression.…”
Section: Dex-induced ␣-Enac Upregulation Occurs Via Binding To Gcr Inmentioning
confidence: 69%
See 3 more Smart Citations